부산시 일부 중학생의 구강보건교육 경험에 따른 구강보건지식과 행동변화 실태조사 - 고보경(Bo-Kyung Go); 강현숙(Hyun-Sook Kang); 이민경(Min-Kyung Lee); 박혜영(Hye-Young Park); 김혜진(Hye-Jin Kim) (한국구강보건과학회지, 2019)
Objectives: The purpose of this study was to examine the effect of toothbrushing instruction and oral education on changing the oral behavior and oral knowledge of students in all grades of middle school. Methods: IRB approval was obtained from March 2018 to December 2018 to protect the subjects ethically. A total of 752 middle school students (grades 1, 2, and 3) in B City D-gu participated in this work. Results: Regarding the frequency of toothbrushing after the education, daily toothbrushing did not occur, once-a-day toothbrushing was reduced to 4.4%, and twice-a-day or more frequent toothbrushing increased by 5.24%. After the education, toothbrushing using the Bass and other recommended methods increased by 25.3%, the use of the horizontal or mixing method increased by 32%, and the use of the vertical or rotary method increased by 6.7%. After lunch, toothbrushing was increased by 15% to 43.9% after education. These results confirmed that the oral education and toothbrushing lessons for the middle school students caused a change in their toothbrushing behavior. Conclusion: Middle school students should be encouraged to change their toothbrushing behavior through oral education. Then, suitable continuous oral education should be prepared. KCI Citation Count: 7